PENGARUH PARTISIPASI, TRANSPARANSI, KOMPETENSI SUMBER DAYA MANUSIA, PENGENDALIAN DAN PROSES PENYUSUNAN ANGGARAN TERHADAP EFEKTIFITAS ANGGARAN (Studi Kasus Pada RS. Bhayangkara AKPOL Semarang) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study examines the influence of participation, transparency, human resource competencies, control and budgeting process against  effectiveness of the hospital budget Bhayangkara AKPOL Semarang. This study was conducted with a population of 58 people. The analysis tool used is multiple linear regression. Based on the results of the hypothesis test, obtained result that budgetary participation, human resource competencies, and  budgeting process partially does not  significantly influence the effectiveness of the hospital budget Bhayangkara AKPOL Semarang, but transparency  and  control variable  positive partially and significant effect. Base on these results can be recommended to the future researchers can complement the shortcomings of this research, particulary regarding the selection of research variables and added  relevant indicators. Keywords : participation, transparency, human resource competencies, controlling, budgeting process, and the effectiveness of the budget.